Halal kit identifier using radio frequency identification technology - Abd Halim, Noor Hafizah Azlin; Mansor, Hasmah; Hasbullah, Nurul Fadzlin (IEEE, 2016)
Halal certification is very crucial these days. In Malaysia, JAKIM plays very important role to certify halal product. Products with halal certification become highest priority in users’ demands in Muslim country, particularly in Malaysia. However, due to the rapid development of advanced technology, irresponsible manufactures resort to produce fake halal to attract Muslim consumers and overshadow their decision. Therefore this project is to develop a halal kit identifier to help consumer to identify the halal status of the product. The main focus of this project is to validate the Halal status for products by using Radio Frequency Identification (RFID) technology to improve the existing systems available nowadays. Using this approach, the Halal status of the product can be easily validated, because every tag that will be embedded into food packages has its unique identification number. From various tests conducted, the portable Halal kit identifier using RFID technology developed in this research is able to help consumers to validate Halal status of products wirelessly in very efficient way.